Formulasi Pengaturan Tata Cara Perizinan Pemanfaatan Kekayaan Intelektual Komunal Sebagai Bentuk Perlindungan Terhadap Komunitas Asal (RechtJiva, 2024)
Indonesia is an archipelago with diverse and abundant traditional cultures. With so many traditional cultures, there is a creation produced by the people of a region (Communal Intellectual Property). From the many cultural diversity in Indonesia with its uniqueness and selling value, it is currently starting to become a special concern of the government to be “sold” to the national and international cultural markets. However, there is currently no procedure for licensing the utilization of Communal Intellectual Property for Commercial. This research aims to analyze the formulation of licensing procedures related to the commercial use of communal intellectual property as a form of protection for the community of origin. This research uses normative juridical methods that are studied with statutory, comparative, and conceptual approaches. Analysis of legal materials used is through analytical descriptive method. With the results of the discussion, it can be concluded that there is an urgency to establish procedures for licensing the utilization of communal intellectual property as a protection of the community of origin in PP KIK. Then there is an appropriate regulatory model for Indonesia, namely by creating a KIK Special State Authority Agency; Determining the benefit sharing mechanism and its amount; Determining the mechanism for Prior Informed Consent; Determining standard clauses in licensing commercial use of KIK; Determining dispute resolution mechanisms.